Pengelolaan Pembelajaran IPA Berbasis Lingkungan Di Mts Negeri Andong - Nugroho, Agung Adi; , Drs. Sofyan Anif, M.Si; , Dr. Sabar Narimo, M.M, M.Pd (2017)
This research has four purpose (1) To describe lesson plan of natural science based on environment in MTsN Andong, (2) To describe learning management of natural science based on environment in MTsN Andong, (3) To describe learning evaluation of natural science based on environment in MTsN Andong. Research methodology used in this research is interview, observation and documentation.the validity of data use triangulation of source, technique of analyzing data use interactive analyzing method. Based on the research done, it can be concluded that first, specific characteristic of natural science's lesson plan in MTsN Andong is in arranging of lesson plan. Natural science teacher improve lesson plan from the result of discustion among natural science teacher, the lesson plan is improve by teacher by exploiting school environment as source of study. It indicates that school environment is very needed by the student in teaching learning process. School environment can contribute toward the student motivation and involvementin learning process. Second, in learning implementation now a days the students is not only as object but also subject so that llearning process is not "teacher center" anymore but "student center". The pattern of interaction which on going more than two direction, not only between teachers and student but it can be between student and student as well as student and environment. When the student doing observation of Mimosa pudica leaves in school garden, the teacher act as fasilitator that is to lead and to help the student in order to have observation. Third, the evaluation of natural science learning based on environment in MTsN Andong is done by using test (pre-test and post-test) and not test such as experiment. The result of study that is gained be the students after learning implementation using environment in movement system of plant can increase it can be seen from two meeting those were first meeting done in the class and second meeting in environment (school garden). At the first meeting the teacher evaluation the students who got lower than minimum standard and at the second meeting there was a development it meant many students got higher mast from the minimum standard.